2010
DOI: 10.4238/vol9-2gmr779
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair genes in endometriosis

Abstract: ABSTRACT. Several polymorphisms in the DNA repair gene are thought to have significant effects on cancer risk. We investigated the association of polymorphisms in the DNA repair genes XRCC1 Arg399Gln, XRCC3 Thr241Met, XPD Lys751Gln, XPG Asp1104His, APE1 Asp148Glu, and HOGG1 Ser326Cys with endometriosis risk. Genotypes were determined by PCR-RFLP assays in 52 patients with endometriosis and 101 age-matched healthy controls. Although there were no significant (P > 0.05) differences in the frequencies of genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…However, the genes that play a role in the susceptibility to and progression of endometriosis remain unknown (Attar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the genes that play a role in the susceptibility to and progression of endometriosis remain unknown (Attar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…В его отношении в литерату-ре известны случаи противоречащих ассоциаций. Так в исследовании R. Attar (2010) генотип гомозиготный по мажорному варианту СС гена XRCC3 был установ-лен как рисковый при формировании эндометриоза у женщин (Attar, et al, 2010). Тогда как по данным T. R. Smith (2003), ассоциация с развитием рака яич-ников была установлена с минорным аллелем Т (Smith, et al, 2003).…”
Section: Discussionunclassified
“…However, the XRCC1 codons 107 and 194 were not associated with susceptibility to endometriosis [3]. In contrast, in a recent study conducted in Turkey, no relation was found between XRCC1 codon 399 polymorphism and endometriosis [11]. …”
Section: Discussionmentioning
confidence: 99%